Disintegration of microtubules in Arabidopsis thaliana and bladder cancer cells by isothiocyanates - Øverby, Anders; Bævre, Mette S.; Thangstad, Ole P.; Bones, Atle M. (Frontiers in Plant Science, 2015)
Isothiocyanates (ITCs) from biodegradation of glucosinolates comprise a group of electrophiles associated with growth-inhibitory effects in plant- and mammalian cells. The underlying modes of action of this feature are not fully understood. Clarifying this has involved mammalian cancer cells due to ITCs’ chemopreventive potential. The binding of ITCs to tubulins has been reported as a mechanism by which ITCs induce cell cycle arrest and apoptosis. In the present study we demonstrate that ITCs disrupt microtubules in Arabidopsis thaliana contributing to the observed inhibited growth phenotype. We also confirmed this in rat bladder cancer cells (AY-27) suggesting that cells from plant and animals share mechanisms by which ITCs affect growth. Exposure of A. thaliana to vapour-phase of allyl ITC (AITC) inhibited growth and induced a concurrent bleaching of leaves in a dose-dependent manner. Transcriptional analysis was used to show an upregulation of heat shock-genes upon AITC-treatment. Transgenic A. thaliana expressing GFP-marked α-tubulin was employed to show a time- and dose-dependent disintegration of microtubules by AITC. Treatment of AY-27 with ITCs resulted in a time- and dose-dependent decrease of cell proliferation and G2/M-arrest. AY-27 transiently transfected to express GFP-tagged α-tubulin were treated with ITCs resulting in a loss of microtubular filaments and the subsequent formation of apoptotic bodies. In conclusion, our data demonstrate an ITC-induced mechanism leading to growth inhibition in A. thaliana and rat bladder cancer cells, and expose clues to the mechanisms underlying the physiological role of glucosinolates in vivo.